Memahami Ketidakmerataan Pendidikan di Desa Kasomalang Wetan: Faktor Penyebab dan Dampaknya - Pitria, Nurfa Izzah; Arip Budiman; A.F. Zikra R Caniago; Fajar Ihsan Kurnia; Mochamad Averoz Maulidio (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
Education in Indonesia, particularly in rural areas, still faces numerous challenges. This article examines the educational disparities in Desa Kasomalang Wetan, focusing on SD Kasomalang IX. The study employs a qualitative research method to identify the factors causing and the impacts of these educational disparities. The findings indicate that these disparities are caused by inadequate infrastructure, facilities, and teaching staff. Teachers at SD Kasomalang IX face an extremely high student-to-teacher ratio, resulting in fragmented and suboptimal learning times. Additionally, limited classroom facilities and outdated educational equipment contribute to the delay in cognitive development and basic skills acquisition among students. The study recommends increasing the number and quality of teaching staff, improving educational infrastructure and facilities, and collaborating with local communities to enhance educational quality in rural areas.